Design and development of microstrip antenna circular patch array for maritime radar applications - Yusnita Rahayu; Iklil Artiyah (Lembaga Studi Pendidikan dan Rekayasa Alam Riau, 2021)
The maritime radar is a mobile station used by ships to cover large areas in Indonesian waters. Maritime radar is used to monitor Indonesia's marine waters. One of the maritime radar subsystems is the antenna. The antenna emits the electromagnetic waves into the air to detect an object. In this study, a 1 × 4 circular patch array microstrip antenna is proposed. This antenna is applied to maritime radar working in the frequency range of 2.2 – 4.2 GHz that are allocated by the Ministry of Communication and Information of the Republic of Indonesia. From the simulation results, the proposed antenna provides a return loss of -66.29 dB, and a gain of 7.14 dB at 3.2 GHz.